Molecular recognition of a carboxy pyridostatin toward G‐quadruplex structures: Why does it prefer RNA?. (6th June 2017) - Rocca, Roberta; Talarico, Carmine; Moraca, Federica; Costa, Giosuè; Romeo, Isabella; Ortuso, Francesco; Alcaro, Stefano; Artese, Anna
Abstract : The pyridostatin (PDS) represents the lead compound of a family of G‐quadruplex (G4) stabilizing synthetic small molecules based on a N, N ′‐bis(quinolinyl)pyridine‐2, 6‐dicarboxamide scaffold. Its mechanism of action involves the induction of telomere dysfunction by competing for binding with telomere‐associated proteins, such as human POT1. Recently, through a template‐directed "in situ " click chemistry approach, a PDS derivative, the carboxypyridostatin ( c PDS), was discovered. It has the peculiarity to exhibit high molecular specificity for RNA over DNA G4, while PDS is a good generic RNA and DNA G4‐interacting small molecule. Structural data on the binding modes of these compounds are not available, and the selectivity mode of c PDS toward TERRA G4 is unknown too. Therefore, this work is aimed at rationalizing the selectivity of c PDS versus TERRA G4 by means of molecular dynamics and docking simulations, coupled to better understand the binding mode of these compounds to telomeric G4 structures. The comprehensive analysis of cPDS binding mode and its conformational behavior demonstrates the importance of the ligand conformation properties coupled with a remarkable solvation contribution. This work is expected to provide valuable clues for further rational design of novel and selective TERRA G4 binders. Abstract : The pyridostatin (PDS) represents the lead compound of a family of G‐quadruplex (G4) stabilizing synthetic small molecules based on a N, N ′‐bis(quinolinyl)pyridine‐2, 6‐dicarboxamide scaffold. Interestingly, a PDS derivative, the carboxypyridostatin ( c PDS), has the peculiarity to exhibit high molecular specificity for RNA over DNA G4. This work is aimed at rationalizing the selectivity of c PDS versus TERRA G4 by means of molecular dynamics and docking simulations, coupled to better understand the binding mode of these compounds to telomeric G4 structures.